Validation of the generic program performance measure for correctional programs - Stewart, Lynn A. (Criminal justice and behavior, 2015)
The Generic Program Performance Measure (GPPM) was developed to assess the progress and performance of offenders participating in correctional programs. Program facilitators use the GPPM to systematically rate offenders? skill development, attitude change, motivation level, and program participation. The present study examined the psychometric properties of the GPPM using a total sample of 3,815 offenders who were assessed on the tool at pre-treatment, and 2,120 who were assessed pre- and post-treatment and subsequently released. Results indicated that the measure was sensitive to significant treatment gain in all program areas: for men and women, and Aboriginal and non-Aboriginal participants. Internal consistency was excellent. Interrater reliability was acceptable. Importantly, offenders who were rated as not demonstrating treatment gain were more likely to return to custody than those who achieved treatment gain. The GPPM is a reliable and valid measure of progress across a range of correctional programs that is not resource intensive.